Avaliação do efeito de injeção de gás na remoção das inclusões em distribuidor de lingotamento contínuo por meio de modelagem matemática - Gisele Márcia de Souza (2019)
The increasing demand for high quality steels requires continuous improvement and strict control of the process by the steel companies. Therefore, the removal of inclusions in the continuous casting tundish has been extensively studied through physical and mathematical modeling. In addition to the flow modifiers, the injection of gas in the tundish has been considered as an alternative to intensify the removal of inclusions. Although there are many studies developed on this technique, there is demand for further investigation regarding the efficiency of removal of inclusions involving the effect of the gas flow, the location of the injection system. The main aim of the present study was to evaluate the efficiency of inclusion removal in a continuous casting tundish with gas injection through mathematical modelling. The model was developed using commercial CFD software ANSYS CFX. A special boundary condition to describe the behaviour of the particles at the free surface was proposed and implemented by a subroutine. The numerical results were validated through the experimental results of MENDONÇA (2016). The results demonstrated that the association of flow modifiers and gas injection system in the tundish does not imply in an improvement of the inclusion removal efficiency. Configurations of tundish without flow modifiers and with gas injection exhibit greater removal efficiency of inclusions for the smaller particles, while the use of the flow modifiers improves the flotation of larger particles. Additional configurations were studied using the mathematical model. The greater removal inclusion efficiency was achieved in the tundish with a dam and the plug positioned at 56cm of distance from the ladle shroud and operating with gas flow rate of 3NL/min.